Electric spark deposition preparation method of W-MoS2 self-lubricating coating and application of W-MoS2 self-lubricating coating in surface strengthening of steel parts

By preparing W-MoS2 self-lubricating coating on the surface of the steel matrix, and optimizing the composition of electrode materials using electric spark deposition technology, the problem of degradation of traditional lubricating materials under extreme operating conditions is solved, and the efficient friction reduction and wear resistance of steel parts is achieved.

CN120119245APending Publication Date: 2025-06-10SHENYANG LIGONG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510278407.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-06-10

AI Technical Summary

Technical Problem

The performance of traditional lubricating materials deteriorates under extreme operating conditions, resulting in severe friction and wear of friction parts, affecting the operating efficiency of the equipment.

Method used

By optimizing the mass ratio of the electrode material W powder to MoS2 powder, an electric spark deposition technology was used to prepare a W-MoS2 self-lubricating coating on the surface of the steel matrix to form a coating with excellent friction reduction and wear resistance.

Benefits of technology

It significantly improves the service performance of steel parts under extreme operating conditions, extends service life, and reduces friction coefficient and wear.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120119245A_ABST
    Figure CN120119245A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of metal surface engineering, and relates to an electric spark deposition preparation method of a W-MoS2 self-lubricating coating and application of the W-MoS2 self-lubricating coating in steel part surface strengthening. According to the method, steel is used as a matrix material, a composite electrode prepared by sintering tungsten powder and molybdenum disulfide powder is adopted, and the W-MoS2 self-lubricating coating with excellent tribological performance is prepared on the surface of a steel matrix by controlling parameters of an electric spark deposition process. The coating and a steel substrate form a good metallurgical bonding interface. A hard phase W in the coating provides excellent bearing capacity, a lubricating phase MoS2 forms a continuous lubricating film in the friction process, and a new phase (such as Mo, WS2 and the like) generated by a high-temperature decomposition reaction of MoS2 in the electric spark deposition process synergistically enhances the antifriction and wear resistance of the coating, the friction coefficient and the wear loss are remarkably reduced compared with a steel matrix, and the wear resistance of the coating is greatly improved. The method is particularly suitable for strengthening the key friction pair surface of high-end mechanical equipment in the modern industrial field and prolonging the service life of steel parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of metal surface engineering, and relates to a method for preparing a W-MoS 2 self-lubricating coating by electric spark deposition and its application in surface strengthening of steel parts. Specifically, by optimizing the mass ratio composition of W powder and MoS 2 powder, a W-MoS 2 self-lubricating coating with excellent friction reduction and wear resistance is prepared on the surface of steel parts. This technology can significantly improve the service performance of steel parts under extreme working conditions and has broad application prospects in the field of high-end equipment manufacturing. Background Art

[0002] With the continuous improvement of the working performance of high-end mechanical equipment in the modern industrial field, key friction pair steel components are facing challenges of extreme working conditions such as a wide temperature range, large contact stress, and complex environmental media. Traditional lubricating materials have a narrow applicable temperature range, poor compressive resistance, and pollute the environment. Under extreme working conditions, the lubricating performance drops sharply, resulting in severe friction and wear of friction parts and seriously affecting the operation efficiency of equipment.

[0003] Solid lubricating coating technology can enhance the surface friction reduction and wear resistance of parts while maintaining their original performance, which is an effective technical means to solve this problem. Among them, transition metal dichalcogenides (TMDs) MoS 2 / WS 2 has a layered structure and is prone to interlayer slip under the action of shear force, resulting in a friction reduction effect. The friction coefficient can be as low as 0.01 in a vacuum environment and is widely used in the surface coating technology of main friction steel parts in modern industrial fields such as aerospace. Although the pure MoS 2 / WS 2 self-lubricating coating has excellent lubricating performance, but it also has problems such as low hardness, poor wear resistance, and environmental sensitivity. Especially in a humid and high-temperature atmosphere, it is prone to decomposition and oxidation, resulting in a decline in lubricating performance. Research shows that doping materials with excellent friction reduction and wear resistance into MoS 2 / WS 2 and adopting a suitable coating preparation technology can prepare a MoS 2 / WS 2 -based solid self-lubricating coating with excellent tribological properties on the surface of steel components, thereby enhancing the protection performance of steel components.

[0004] Currently, MoS 2 / WS 2The commonly used preparation techniques for self-lubricating coatings mainly include thermal spraying, laser cladding, magnetron sputtering, and electro-discharge deposition techniques. Among them, the electro-discharge deposition technique has become a research hotspot due to its unique working principle. This technique melts and deposits the electrode material onto the substrate surface through instantaneous pulsed electrical energy. During this process, intense diffusion and re-alloying occur between the electrode and the workpiece material, thereby forming a high-strength metallurgical bond between the coating and the substrate. Compared with other techniques, the electro-discharge deposition technique has the advantages of simple process, low cost, low heat input, high bonding strength, and relatively thick coatings. Research shows that the coatings prepared by the electro-discharge deposition technique significantly improve the friction and wear performance of the substrate, providing important technical support for its wide application in the industrial field.

[0005] The Chinese invention patent application (publication number CN117966071A) proposes a method for preparing a self-lubricating coating of W-WS 2 by electro-discharge deposition, using a sintered electrode containing a solid lubricant for the electro-discharge deposition of a self-lubricating coating with a W-WS 2 anti-friction and lubricating phase. The obtained self-lubricating coating can solve the friction and wear problems on the surface of steel substrate materials in friction and wear environments. Its disadvantages are that WS 2 has low reserves in nature, high cost, and is extremely prone to agglomeration, resulting in poor coating uniformity and reduced lubrication performance. Summary of the Invention

[0006] The purpose of the present invention is to provide a method for preparing a self-lubricating coating of W-MoS 2 by electro-discharge deposition and its application in the surface strengthening of steel parts. This method uses a mixture of W and MoS 2 powders sintered into an electrode, and prepares a W-MoS 2 self-lubricating coating on the surface of a steel substrate through the electro-discharge deposition technique to reduce the friction and wear on the surface of key friction steel components of high-end mechanical equipment, thereby improving the operating efficiency of the equipment and extending the service life of steel components.

[0007] The technical solution of the present invention is as follows:

[0008] A method for preparing a self-lubricating coating of W-MoS 2 by electro-discharge deposition, using steel as the substrate material, and using a W-MoS 2 composite material sintered from W powder with an average particle size of 2 μm and MoS 2 powder as the electro-discharge electrode through plasma sintering technology. The steel substrate and the electro-discharge electrode are pretreated, and then a W-MoS 2 self-lubricating coating is deposited on the surface of the steel substrate by electro-discharge technology.

[0009] The described W-MoS 2Method for preparing self-lubricating coating by electro-discharge deposition, comprising the following steps:

[0010] (1) Preparation of W-MoS 2 composite material

[0011] Mix W powder and MoS 2 powder evenly according to the mass ratio of (70-90):(30-10), and then use the plasma sintering technology to heat from room temperature to 1500°C at a heating rate of 50°C / min and sinter for 20 min under the parameters of a pressure of 45 MPa to prepare W-MoS 2 composite material as the electro-discharge electrode material;

[0012] (2) Surface pretreatment

[0013] Process the steel substrate into a cuboid, and process the W-MoS 2 composite material into a cylindrical bar suitable for clamping in electro-discharge deposition. Grind the steel substrate and the electro-discharge electrode step by step with 240#, 600#, 800#, and 1000# sandpapers to remove the surface oxide film, and then perform ultrasonic cleaning with absolute ethanol for 10 min to remove the surface oil stain;

[0014] (3) Electro-discharge deposition

[0015] Perform electro-discharge deposition of W-MoS 2 self-lubricating coating on the surface of the steel substrate under argon protection. The optimized specific deposition parameters are: output power 1200 W, output voltage 80 V, electrode rotation speed 3000 r / min, deposition rate 1 min / cm 2 , and argon flow rate 15 L / min.

[0016] In the method for preparing the self-lubricating coating by electro-discharge deposition of W-MoS 2 as described above, in step (1), by changing the mass ratio of W powder and MoS 2 powder in the composite material electrode, the phase composition and distribution of the self-lubricating coating are adjusted, so as to optimize the mechanical properties and tribological properties of the coating.

[0017] In the method for preparing the self-lubricating coating by electro-discharge deposition of W-MoS 2 as described above, in step (1), the particle size range of W powder and MoS 2 powder is 1-3 μm.

[0018] In the method for preparing the self-lubricating coating by electro-discharge deposition of W-MoS 2 as described above, in step (2), the steel substrate material is CrNi3MoVA steel, 45# steel or Q235 steel.

[0019] In the method for preparing the self-lubricating coating by electro-discharge deposition of W-MoS 2Electrical discharge deposition preparation method of self-lubricating coating. When the mass ratio of W powder to MoS 2 powder is 80:20, part of MoS in the electrical discharge electrode 2 decomposes and generates WS with more excellent lubrication performance 2 , and the coating is composed of W, Mo, MoS 2 and WS 2 phases, in-situ generating new reinforcement phases of Mo and WS 2 , and MoS 2 , WS 2 show a tendency of (002) preferred orientation.

[0020] For the electrical discharge deposition preparation method of the W-MoS 2 self-lubricating coating, the thickness of the W-MoS 2 self-lubricating coating is 20 - 40 μm.

[0021] For the application of the W-MoS 2 self-lubricating coating in the surface strengthening of steel parts, the W-MoS 2 self-lubricating coating significantly improves the service performance of steel parts under extreme working conditions and extends the service life of steel parts.

[0022] For the application of the W-MoS 2 self-lubricating coating in the surface strengthening of steel parts, by systematically verifying the surface protection performance of the W-MoS 2 self-lubricating coating for different types of steel parts to meet the service requirements of modern industrial fields such as aerospace, military equipment or high-end machinery.

[0023] For the application of the W-MoS 2 self-lubricating coating in the surface strengthening of steel parts, the W-MoS 2 self-lubricating coating is suitable for the surface strengthening of key moving steel parts in modern industrial fields, including: firearm parts or armor components in the military field, high-temperature bearings or precision guides in the aerospace field, steam turbine blades in the power industry, and drilling tools or valve components in the petroleum industry.

[0024] The design concept of the present invention is:

[0025] Although the solid lubricant material MoS 2 / WS 2 has excellent lubrication performance, its hardness is low, and it is prone to decomposition and oxidation reactions in high-temperature and humid air environments, resulting in a significant decline in the tribological performance of the pure MoS 2 / WS 2 coating. To solve this defect, the present invention incorporates the high-strength, high-pressure-resistant, and corrosion-resistant metal material W into the solid lubricating soft material MoS 2Among them, metal W has a preferential oxidation property in the atmospheric environment to improve the hardness and oxidation resistance of its coating. In addition, W and Mo are elements of the same group. According to the principle of thermodynamics, MoS 2 During the process of electro-spark deposition coating, due to high-temperature decomposition, it can react with W to generate WS 2 , and the in-situ generated WS 2 can effectively avoid its agglomeration, and its lubricating performance is better than that of MoS 2 . Therefore, the two have good compatibility. At the same time, during the process of electro-spark deposition coating, through the mutual inhibition of the grains of different component materials, the lattice slip of MoS 2 is hindered, the grain refinement is realized, and the mechanical properties of the coating are enhanced by means of the high-strength metallurgical bonding and solid solution strengthening advantages between the coating and the substrate, so as to significantly improve the friction reduction and wear resistance performance of the coating.

[0026] The present invention uses steel as the substrate material, and a composite electrode prepared by sintering tungsten powder and molybdenum disulfide powder. By controlling the electro-spark deposition process parameters, a W-MoS 2 self-lubricating coating with excellent tribological properties is prepared on the surface of the steel substrate. The coating forms a good metallurgical bonding interface with the steel substrate. The hard phase W in the coating provides excellent load-bearing capacity, and the lubricating phase MoS 2 forms a continuous lubricating film during the friction process, and the new phases (such as Mo, WS 2 etc.) generated by the high-temperature decomposition reaction of MoS 2 during the electro-spark deposition process synergistically enhance the friction reduction and wear resistance performance of the coating. The friction coefficient and wear amount are significantly reduced compared with the steel substrate, and it is especially suitable for the surface strengthening of key friction pairs of high-end mechanical equipment in the modern industrial field.

[0027] The advantages and beneficial effects of the present invention are as follows:

[0028] 1. The element Fe of the steel substrate of the self-lubricating coating developed by the present invention diffuses into the coating, and the coating forms a metallurgical bond with the steel substrate, and the bonding force is strong;

[0029] 2. In the present invention, the metal W element can effectively make up for the defects of easy decomposition and oxidation of MoS 2 ;

[0030] 3. The incorporation of the metal W element in the present invention can significantly improve the mechanical properties of the coating, and the prepared W-MoS 2 self-lubricating coating has significantly enhanced wear resistance and resistance to plastic deformation compared with the steel substrate;

[0031] 4. The self-lubricating coating developed by the present invention has a good friction reduction and wear resistance effect, and the average friction coefficient is reduced to about 0.1, and the wear amount is significantly reduced compared with the steel substrate.

[0032] 5. The W-MoS 2The preparation process of self-lubricating coating is simple, easy to operate, low cost, green and environmentally friendly, and easy to realize industrial application;

[0033] 6. The present invention forms a solid self-lubricating coating with excellent friction reduction and wear resistance on the surface of the substrate by adjusting the ratio of electrode materials, thereby significantly improving the surface performance and service life of key friction steel parts of high-end mechanical equipment.

[0034] In summary, the present invention incorporates W powder into MoS 2 In powder, W-MoS prepared by combining the advantages of electrospark deposition coating technology 2 The self-lubricating coating has excellent friction reduction and wear resistance, and can solve the severe friction and wear problems of key friction steel components in high-end mechanical equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 Electrospark deposition of W-MoS on CrNi3MoVA steel surface 2 Surface morphology of self-lubricating coatings;

[0036] Figure 2 Electrospark deposition of W-MoS on CrNi3MoVA steel surface 2 Energy dispersive spectrometry (EDS) surface scanning results of self-lubricating coatings;

[0037] Figure 3 Electrospark deposition of W-MoS on CrNi3MoVA steel surface 2 EDS point scanning results of self-lubricating coating; where (a) represents Figure 1 The position spectrum of the white “spherical tumor” shaped object marked 24, (b) represents Figure 1 The position spectrum of the white “bulb” shaped object marked 25;

[0038] Figure 4 Electrospark deposition of W-MoS on CrNi3MoVA steel surface 2 Cross-sectional morphology of the self-lubricating coating (a) and EDS line scan results (b);

[0039] Figure 5 Electrospark deposition of W-MoS on CrNi3MoVA steel surface 2 X-ray diffraction (XRD) spectrum of the self-lubricating coating, the abscissa 2θ is the diffraction angle (degree), and the ordinate Relative Intensity is the relative intensity (au);

[0040] Figure 6 CrNi3MoVA steel with surface electrospark deposited W-MoS 2 Mechanical properties test results of CrNi3MoVA steel with self-lubricating coating, the horizontal axes are CrNi3MoVA steel and W-MoS2 Self-lubricating coating, with Elastic Modulus (GPa) on the left vertical axis and Hardness (GPa) on the right vertical axis;

[0041] Figure 7 For CrNi3MoVA steel and surface electro-discharge deposited W-MoS 2 Test comparison results of the friction coefficient of CrNi3MoVA steel with self-lubricating coating, with Time (min) on the horizontal axis and Friction coefficient on the vertical axis;

[0042] Figure 8 For CrNi3MoVA steel and surface electro-discharge deposited W-MoS 2 Test comparison results of the wear amount of CrNi3MoVA steel with self-lubricating coating, with CrNi3MoVA steel and W-MoS on the horizontal axis respectively 2 Self-lubricating coating, with Wear weight loss (mg) on the vertical axis;

[0043] Figure 9 For CrNi3MoVA steel and surface electro-discharge deposited W-MoS 2 Wear morphology of CrNi3MoVA steel with self-lubricating coating; among them, (a) represents CrNi3MoVA steel and (b) represents W-MoS 2 Self-lubricating coating. Specific implementation manners

[0044] In the specific implementation process, the present invention mixes W powder with an average particle size of 2 μm and MoS 2 powder evenly according to the mass ratio of (70-90):(30-10), and then uses plasma sintering technology to prepare W-MoS 2 composite material. This composite material is used as the electro-discharge electrode, and the steel matrix material and the electrode material are pretreated. Subsequently, under argon protection according to the optimized deposition parameters, W-MoS is deposited on the surface of the steel matrix by electro-discharge deposition technology 2 Self-lubricating coating.

[0045] Next, the present invention will be further described in detail with reference to the drawings and embodiments.

[0046] Example 1

[0047] In this example, the matrix material is CrNi3MoVA steel, and W powder with an average particle size of 2 μm and MoS 2 powder are mixed evenly according to the mass ratio of 80:20 respectively. The preparation steps of the W-MoS 2 self-lubricating coating are as follows:

[0048] (1) The uniformly mixed W powder and MoS 2 powder are sintered into a W-MoS 2 composite material by plasma sintering technology under the parameters of a pressure of 45 MPa, heating from room temperature to 1500 °C at a heating rate of 50 °C / min, and a sintering time of 20 min, so as to be used as an electric discharge machining electrode material;

[0049] (2) The CrNi3MoVA steel is processed into a cuboid with dimensions of 20 mm × 10 mm × 5 mm, and the W-MoS 2 composite material is processed into a Φ4 mm × 50 mm columnar rod suitable for electric discharge deposition clamping. The substrate and the electrode material are polished step by step with 240#, 600#, 800#, and 1000# sandpapers to remove the surface oxide film, and then ultrasonically cleaned with anhydrous ethanol for 10 min to remove the surface oil stain;

[0050] (3) An argon-protected W-MoS 2 self-lubricating coating is deposited on the surface of CrNi3MoVA steel. The specific deposition parameters are: output power 1200 W, output voltage 80 V, electrode rotation speed 3000 r / min, deposition rate 1 min / cm 2 , and argon flow rate 15 L / min.

[0051] As Figure 1 shown, the surface morphology of the W-MoS 2 self-lubricating coating deposited on the surface of CrNi3MoVA steel is shown. The grain size is shown in Table 1. It can be seen from Figure 1 that the surface of the self-lubricating coating exhibits typical stacking and sputtering characteristics of the electric discharge deposition process. Table 1 shows that the coating grains are refined to the nanoscale, forming an ultrafine grain structure.

[0052] Table 1 is a statistical table of the crystal phase content and grain size of the W-MoS 2 self-lubricating coating deposited on the surface of CrNi3MoVA steel

[0053]

[0054] As Figure 2 shown, the EDS surface scanning result of the W-MoS 2 self-lubricating coating deposited on the surface of CrNi3MoVA steel is shown. It can be seen from Figure 2 that a small amount of O element is detected in the coating, indicating that although there is argon protection during the electric discharge deposition of the coating, a small amount of O is still involved, and the coating contains Fe element, indicating that the Fe element in CrNi3MoVA steel diffuses into the coating.

[0055] As Figure 3As shown, the W-MoS self-lubricating coating was deposited on the surface of CrNi3MoVA steel by electric spark deposition 2 EDS point scanning results of the self-lubricating coating, from Figure 3 It can be seen that the main component of the white "ball tumor" is W, and the content of W element in the gray component decreases significantly

[0056] As Figure 4 shown, the W-MoS self-lubricating coating was deposited on the surface of CrNi3MoVA steel by electric spark deposition 2 Cross-sectional morphology and EDS line scanning results of the self-lubricating coating, from Figure 4 It can be seen that the coating structure is dense. The white metal W element is mainly concentrated in the middle and lower parts of the coating, with little difference in properties from the CrNi3MoVA steel matrix and good compatibility. Therefore, the W-MoS 2 coating has good metallurgical bonding with the CrNi3MoVA steel matrix and strong bonding force. The coating thickness is about 25±5μm. The Fe element and the W, Mo, S, and O elements show a gradient transition at the coating-matrix interface, indicating that a high-strength metallurgical bond is formed between the coating and the matrix

[0057] As Figure 5 shown, the W-MoS self-lubricating coating was deposited on the surface of CrNi3MoVA steel by electric spark deposition 2 XRD pattern of the self-lubricating coating, from Figure 5 It can be seen that part of the MoS 2 decomposes and generates WS with better lubrication performance 2 , and the coating is composed of W, Mo, MoS 2 and WS 2 phases, and new enhanced phases of Mo and WS 2 are in-situ generated. MoS 2 , WS 2 show a (002) preferred orientation trend, and no oxides or other substances are detected. This is because the contents of O and Fe elements are low, and the contents of the products formed by these elements in the coating are extremely small, so the XRD pattern results do not show

[0058] As Figure 6 shown, mechanical property test results of CrNi3MoVA steel with the W-MoS self-lubricating coating deposited on its surface, from 2 It can be seen that the hardness (H), elastic modulus (E), the ratio of hardness to elastic modulus (H / E), and the ability to resist plastic deformation (H Figure 6 / E 3 / E 2 ) increase to 9.99 GPa, 244.6 GPa, 0.041, and 0.017 respectively. Compared with the CrNi3MoVA steel matrix, H, E, and H / E increase by 74%, 9.6%, and 57.7% respectively, and H 3 / E2 It is increased by 3.5 times, and the wear resistance and the ability to resist plastic deformation are significantly enhanced compared with the CrNi3MoVA steel matrix.

[0059] A high-speed reciprocating friction and wear tester of type HSR-2M was used to conduct friction and wear tests on CrNi3MoVA steel and CrNi3MoVA steel with a surface electro-discharge deposited W-MoS 2 self-lubricating coating. Test parameters: The counterbody was a 304 stainless steel ball with a diameter of Φ6 mm, the load was 6 N, the reciprocating distance was 7 mm, the reciprocating friction frequency was 500 times / min, the friction time was 10 min. An electronic balance with a precision of 0.01 mg was used to weigh the mass of the specimen before and after the friction and wear test, and the wear mass loss was calculated. As Figure 7 shown, the test comparison results of the friction coefficients of CrNi3MoVA steel and CrNi3MoVA steel with a surface electro-discharge deposited W-MoS 2 self-lubricating coating. It can be seen from Figure 7 that the running-in period of the friction coefficient of the CrNi3MoVA steel matrix is long, the fluctuation range is large, and the average friction coefficient is 0.6, while the running-in period of the W-MoS 2 self-lubricating coating is extremely short. After the friction starts, it quickly enters the stable stage, the fluctuation range is small, and the average friction coefficient is only 0.109. As Figure 8 shown, the test comparison results of the wear amounts of CrNi3MoVA steel and CrNi3MoVA steel with a surface electro-discharge deposited W-MoS 2 self-lubricating coating. It can be seen from Figure 8 that the wear weight loss of the CrNi3MoVA steel is 3.2 mg, while the wear weight loss of the CrNi3MoVA steel with the electro-discharge deposited W-MoS 2 self-lubricating coating is 1.18 mg. Compared with the CrNi3MoVA steel matrix, the friction coefficient is reduced by 82%, and the wear amount is reduced by 63%.

[0060] As Figure 9 shown, the surface wear morphologies of CrNi3MoVA steel and CrNi3MoVA steel with a surface electro-discharge deposited W-MoS 2 self-lubricating coating. It can be seen from Figure 9 that under the action of a 6 N load, significant plastic deformation occurs on the surface of the CrNi3MoVA steel matrix to form a plough groove morphology. As the friction continues, microcracks initiate and expand in the surface stress concentration region, resulting in local shear fracture of the material surface, leading to large-area spalling of the surface layer material, and at the same time, a large amount of wear debris is generated. The wear mechanism is mainly manifested as the synergistic effect of abrasive wear and fatigue wear. W-MoS 2The self-lubricating coating exhibits excellent friction reduction and wear resistance during the friction process. Only a small amount of slight ploughing grooves are generated on the worn surface. Its excellent performance stems from the unique multi-scale synergistic mechanism of hard and soft phases: First, as the friction process continues, the layered MoS 2 and WS 2 lubricating phases, supported by the W and Mo hard-phase skeletons, undergo directional slip and rearrangement through the lattice distortion of the (002) crystal plane and the transformation of structural order, forming a continuous lubricating film with self-repair characteristics. Second, the hard phases play a synergistic effect through the following multiple mechanisms: The mechanical support effectively inhibits the extrusion loss of the lubricating phase; the micro-ploughing effect generated by the moderately exposed hard-phase protrusions promotes the formation of shallow ploughing grooves on the surface; the stress gradient distribution at the hard-phase / lubricating-phase interface delays the initiation and propagation of cracks. Therefore, the wear mechanism of this coating is mainly adhesive wear dominated by the lubricating phase and slight abrasive wear caused by the hard phases. This multi-scale synergistic design strategy of hard and soft phases provides an important theoretical guidance and technical approach for the development of a new generation of high-performance self-lubricating coatings.

[0061] Example 2

[0062] In this example, the substrate material is 45 steel. W powder with an average particle size of 2 μm and MoS 2 powder are mixed evenly according to a mass ratio of 70:30 respectively. The preparation steps of the W-MoS 2 self-lubricating coating are as follows:

[0063] (1) The evenly mixed W powder and MoS 2 powder are sintered into a W-MoS 2 composite material by using plasma sintering technology under the parameter conditions of a pressure of 45 MPa, heating from room temperature to 1500 °C at a heating rate of 50 °C / min, and a sintering time of 20 min to be used as the electric discharge machining electrode material.

[0064] (2) The 45 steel is processed into a cuboid with dimensions of 20 mm × 10 mm × 5 mm, and the W-MoS 2 composite material is processed into a Φ4 mm × 50 mm columnar rod suitable for clamping in electric discharge deposition. The substrate and the electrode material are polished step by step with 240#, 600#, 800#, and 1000# sandpapers to remove the surface oxide film, and then ultrasonically cleaned with absolute ethanol for 10 min to remove the surface oil stain.

[0065] (3) Under argon protection, a W-MoS 2 self-lubricating coating is deposited on the surface of the 45 steel. The specific deposition parameters are: output power 1200 W, output voltage 80 V, electrode rotation speed 3000 r / min, deposition rate 1 min / cm 2 , and argon flow rate 15 L / min.

[0066] Deposit W-MoS 2 self-lubricating coating on the surface of 45 steel substrate. The coating forms an ultrafine grain structure, has good bonding with the substrate, and the thickness of the self-lubricating coating is about 35μm. The coating consists of W, Mo and MoS 2 , WS 2 phases. MoS 2 , WS 2 shows a tendency of (002) preferred orientation. The content of lubricating phases MoS 2 , WS 2 in the coating is significantly increased compared with the 80:20 mixing ratio of W powder and MoS 2 powder in Example 1. H, E, H / E and H 3 / E 2 are 6.29GPa, 165.8GPa, 0.038 and 0.0091 respectively.

[0067] The friction and wear test is carried out by using an HSR-2M type high-speed reciprocating friction and wear tester. Test parameters: The counterbody is a 304 stainless steel ball with a diameter of Φ6mm, the load is 6N, the reciprocating distance is 7mm, the reciprocating friction frequency is 500 times / min, and the friction time is 10min. An electronic balance with a precision of 0.01mg is used to weigh the mass of the specimen before and after the friction and wear test, and the wear mass loss is calculated. After testing, the stable friction coefficient of 45 steel is 0.70 - 0.75, and the wear weight loss is 2.5mg. While for the 45 steel with the W-MoS 2 self-lubricating coating deposited by electric spark, the stable friction coefficient is only 0.1 - 0.2, and the wear weight loss is reduced to 2.44mg.

[0068] Example 3

[0069] In this example, the substrate material is Q235 steel. W powder with an average particle size of 2μm and MoS 2 powder are mixed evenly according to the mass ratio of 90:10 respectively. The preparation steps of the W-MoS 2 self-lubricating coating are as follows:

[0070] (1) The evenly mixed W powder and MoS 2 powder are sintered into W-MoS 2 composite material by using plasma sintering technology under the parameter conditions of a pressure of 45MPa, heating from room temperature to 1500℃ at a heating rate of 50℃ / min, and a sintering time of 20min, so as to be used as the electric spark electrode material;

[0071] (2) The Q235 steel is processed into a cuboid with dimensions of 20mm×10mm×5mm. W-MoS 2The composite material is processed into a Φ4mm×50mm columnar rod suitable for clamping in electro-discharge deposition. The substrate and electrode material are polished step by step with 240#, 600#, 800#, and 1000# sandpapers to remove the surface oxide film, and then ultrasonically cleaned with absolute ethanol for 10 min to remove the surface oil stain;

[0072] (3) Under argon protection, deposit W-MoS 2 self-lubricating coating on the surface of Q235 steel. The specific deposition parameters are: output power 1200W, output voltage 80V, electrode rotation speed 3000r / min, deposition rate 1min / cm 2 , and argon flow rate 15L / min.

[0073] Deposit W-MoS 2 self-lubricating coating on the surface of Q235 steel substrate. The self-lubricating coating forms an ultrafine grain structure and has good bonding with the substrate. The thickness of the self-lubricating coating is about 25±5μm. During the process of preparing the coating by electro-discharge, MoS 2 is completely decomposed and oxidized. The coating is composed of W, Mo, and FeWO 4 phases, generating hard phase Mo and oxygen-containing salts FeWO 4 newly formed phases. The content of the lubricating phase in the coating is significantly reduced compared with the coating with a high MoS 2 content. H, E, H / E, and H 3 / E 2 are 6.93GPa, 204.7GPa, 0.034, and 0.0079 respectively.

[0074] The friction and wear test is carried out by using an HSR-2M type high-speed reciprocating friction and wear testing machine. The test parameters are: the counterbody is a Φ6mm 304 stainless steel ball, the load is 6N, the reciprocating distance is 7mm, the reciprocating friction frequency is 500 times / min, and the friction time is 10min. An electronic balance with an accuracy of 0.01mg is used to weigh the mass of the specimen before and after the friction and wear test, and the wear mass loss is calculated. After testing, the stable friction coefficient of Q235 steel is 0.73 - 0.77, and the wear weight loss is 2.7mg. While for the Q235 steel with the electro-discharge deposited W-MoS 2 self-lubricating coating, the stable friction coefficient is 0.1 - 0.4, and the wear weight loss is only 0.18mg.

[0075] The results of the examples show that the self-lubricating coating of the present invention has a strong metallurgical bond with the steel substrate. W enhances the hardness of the self-lubricating coating, and MoS 2The self-lubricating coating enhances the anti-friction and lubrication effects. The self-lubricating coating obtained by this process has excellent anti-friction and wear-resistant properties, is easy to control, and is suitable for industrial applications. In particular, in the embodiment of the present invention, the composite material electrode optimized with the mass ratio of tungsten powder to tungsten disulfide powder being 80:20, under the process parameters of output power 1200W, output voltage 80V, electrode rotation speed 3000r / min, and deposition rate 1min / cm 2 , the W-MoS 2 self-lubricating coating H, E, H / E, and H 3 / E 2 are up to 6.29GPa, 165.8GPa, 0.038, and 0.0091 respectively. Compared with the steel substrate, after the friction starts, it quickly enters the stable stage, with a small fluctuation range, the average friction coefficient is as low as 0.109, the wear amount is significantly reduced, and the tribological performance is the best.

[0076] The comprehensive experimental characterization and performance evaluation results show that the W-MoS 2 self-lubricating coating developed in the present invention forms a strong metallurgical bonding interface with the steel substrate. Through the multi-scale synergistic effects of W, MoS 2 and the newly formed reinforcing phases, the coating realizes the synergistic optimization of mechanical properties and tribological properties. In particular, the composite electrode mixed and sintered with W powder and MoS 2 powder with a mass ratio of 80:20, under the optimized process parameters (output power 1200W, output voltage 80V, electrode rotation speed 3000r / min, deposition rate 1min / cm 2 , argon protection flow rate 15L / min), the coating prepared by the electrospark deposition technology enters the ultra-stable friction stage after a very short initial running-in stage, with a small fluctuation range of the friction coefficient, and always maintains excellent friction stability during long-term service, showing excellent service performance:

[0077] (1) In terms of mechanical properties, the support structure constructed by W and the newly formed reinforcing phase Mo enables the nano-hardness H of the coating to reach 9.99GPa, the elastic modulus E = 244.6GPa, H / E = 0.041, H 3 / E 2 = 0.017. Compared with the CrNi3MoVA steel substrate, the hardness is increased by 43%, the anti-plastic deformation ability is increased by 57.7%, and the anti-impact performance is increased by 3.5 times;

[0078] (2) In terms of tribological properties, the MoS 2 phase forms a lubricating film with low shear strength through the friction-induced reorientation of the (002) crystal plane, reducing the average friction coefficient to 0.109 and the wear amount to 1.18mg, which are reduced by about 82% and 63% respectively compared with the CrNi3MoVA steel substrate.

[0079] This excellent friction stability is mainly attributed to the self - adaptive lubrication mechanism formed by the coating. The layered MoS 2 / WS 2 soft phase, supported by the W and Mo hard phase skeletons, can effectively maintain the integrity and continuity of the lubricating film on the surface of the friction pair during the dynamic friction process. The preparation technology process of the self - lubricating coating described in the present invention is simple, low - cost, and environmentally friendly, and has significant advantages in industrial application. It is especially suitable for surface strengthening of key moving steel components in modern industrial fields such as firearm parts and armor components in the military industry, high - temperature bearings and precision guide rails in the aerospace field, steam turbine blades in the power industry, and drilling tools and valve components in the petroleum industry. Through this technology, the friction - reducing and wear - resistant performance of steel components under extreme working conditions can be significantly enhanced, the reliability of equipment can be improved, and the maintenance cost can be reduced. It has important industrial application value and broad market prospects. The above embodiments are only used to illustrate the technical solutions of the present invention and cannot be used to limit the scope of the claimed rights of the present invention. Any implementation scheme achieved by parameter optimization, structural improvement, etc. based on the core technical solution of the present invention falls within the protection scope of the present invention.

Claims

1. A method for preparing a W-MoS2 self-lubricating coating by electrospark deposition, characterized in that: Steel is used as the matrix material, and the W-MoS2 composite material sintered by W powder and MoS2 powder with an average particle size of 2μm is used as the electric spark electrode. The steel matrix and the electric spark electrode are pretreated, and then the W-MoS2 self-lubricating coating is deposited on the surface of the steel matrix using the electric spark technology.

2. The method for preparing the W-MoS2 self-lubricating coating by electrospark deposition according to claim 1, characterized in that: The steps include: (1) Preparation of W-MoS2 composite materials W powder and MoS2 powder were mixed evenly in a mass ratio of (70-90): (30-10), and then plasma sintering technology was used to heat the mixture from room temperature to 1500°C at a heating rate of 50°C / min and sintered for 20 minutes at a pressure of 45 MPa to prepare a W-MoS2 composite material as an electrospark electrode material; (2) Surface pretreatment The steel substrate was processed into a cuboid, and the W-MoS2 composite material was processed into a cylindrical bar suitable for electrospark deposition clamping. The steel substrate and the electrospark electrode were polished step by step with 240#, 600#, 800#, and 1000# sandpaper to remove the surface oxide film, and then ultrasonically cleaned with anhydrous ethanol for 10 minutes to remove the surface oil stains. (3) Electrospark deposition W-MoS2 self-lubricating coating was deposited on the surface of steel substrate by electrospark deposition under argon protection. The specific deposition parameters after optimization were: output power 1200W, output voltage 80V, electrode speed 3000r / min, deposition rate 1min / cm 2 , argon flow rate 15L / min.

3. The method for preparing the W-MoS2 self-lubricating coating by electrospark deposition according to claim 2, characterized in that: In step (1), the phase composition and distribution of the self-lubricating coating are adjusted by changing the mass ratio of W powder to MoS2 powder in the composite electrode, thereby optimizing the mechanical properties and tribological properties of the coating.

4. The method for preparing the W-MoS2 self-lubricating coating by electrospark deposition according to claim 2, characterized in that: In step (1), the particle size range of W powder and MoS2 powder is 1 to 3 μm.

5. The method for preparing the W-MoS2 self-lubricating coating by electrospark deposition according to claim 2, characterized in that: In step (2), the steel matrix material is CrNi3MoVA steel, 45 steel or Q235 steel.

6. The method for preparing the W-MoS2 self-lubricating coating by electrospark deposition according to claim 2, characterized in that: When the mass ratio of W powder to MoS2 powder is 80:20, part of the MoS2 in the EDM electrode decomposes and generates WS2 with better lubrication performance. The coating is composed of W, Mo, MoS2 and WS2 phases, and new reinforcing phases of Mo and WS2 are generated in situ. MoS2 and WS2 show a (002) preferred orientation trend.

7. The method for preparing the W-MoS2 self-lubricating coating by electrospark deposition according to claim 2, characterized in that: The thickness of the W-MoS2 self-lubricating coating is 20 to 40 μm.

8. Use of the W-MoS2 self-lubricating coating according to any one of claims 1 to 7 in surface strengthening of steel parts, characterized in that: W-MoS2 self-lubricating coating significantly improves the service performance of steel parts under extreme working conditions and extends the service life of steel parts.

9. The use of the W-MoS2 self-lubricating coating according to claim 8 in surface strengthening of steel parts, characterized in that: The surface protection performance of W-MoS2 self-lubricating coating on different types of steel parts is systematically verified to meet the service requirements of modern industrial fields such as aerospace, military equipment or high-end machinery.

10. The use of the W-MoS2 self-lubricating coating according to claim 8 in surface strengthening of steel parts, characterized in that: W-MoS2 self-lubricating coating is suitable for surface strengthening of key moving steel parts in modern industrial fields, including: gun parts or armor parts in the military field, high-temperature bearings or precision guide rails in the aerospace field, turbine blades in the power industry, and drilling tools or valve parts in the petroleum industry.

Citation Information

Patent Citations

  • Electric spark deposition preparation method of W-WS2 self-lubricating coating

    CN117966071A